Optimized‐Surface Wettability: A New Experimental 3D Modeling Approach Predicting Favorable Biomaterial–Cell Interactions. Issue 7 (14th May 2019) - do Nascimento, Rodney Marcelo; Sarig, Udi; da Cruz, Nilson Cristino; de Carvalho, Vanessa Rafaela; Eyssartier, Camille; Siad, Larbi; Ganghoffer, Jean‐François; Hernandes, Antônio Carlos; Rahouadj, Rachid
Abstract: Despite several decades of research on biomedical implant materials, the identification of predictive and robust in vitro characteristics of cell support ability and viabilities—as indicators of biocompatibility and future implant‐tissue integration—remain elusive. This study addresses the phenomenology of cell–implant interfaces based on experimental, theoretical, and numerical analysis of cell response to functionalized bioceramic coatings of commercial titanium implants, cp‐Ti. A variable spectrum of coatings having differing surface wettabilities, with optimized solid tension values, is obtained. Measured values are modeled and correlated to cell support ability and viabilities. The contributions of different surface aspects to cell viability are decoupled, resulting in the identification of the polar component of the surface free energy as a significant and major cell–substrate effector. Furthermore, results of this study and the suggested model establish the thermodynamic interfacial free energy as an omnipotent measure that can be fully correlated to the morphology of an individual cell under numerical simulation matching empirical observations. Collectively, the 3D model reported herein can offer a new generic theoretical framework, using implementable mathematical simulation, toward the objective of rational biomaterial design that can improve next‐generation metal and ceramic implants. Abstract : New 3D cell–droplet modeling suggests an omnipotent cell morphology mathematical modulator, an interfacial operator Γ, as a generic theoretical framework predicting robust conditions for successful biomedical implant–cell response and tissue ingrowth. Using an optimal wettability window concept and standard, easily‐measurable wetting angles (°), the author's model explains common interacting cell geometric parameters, toward rational next‐generation biomaterial designs.